Efficient methodology for analyzing head disk interface with application to unloading process - Liu, Yan (2011)
Head disk interfaces (HDI) and Load/Unload (L/UL) processes have been studied numerically for over a decade. Several simplified and comprehensive models have been developed to study the HDI in L/UL processes. All existing methods simulated the L/UL behaviors of a slider by iteratively obtaining the instantaneous attitude of a slider through repeatedly solving a modified Reynolds equation which is coupled with the dynamics of the suspension. Despite its relative accuracy, this approach requires huge amount of computational time and power. Hence, developing a simple and efficient model, which is capable of modeling the behavior of the head-disk interface during the L/UL processes, is desired and critical to aid the design process of slide/suspension systems. In this dissertation, a simple but fairly efficient and accurate method was proposed to model and analyze the unloading behavior of a subambient pressure slider. A dual scale model for head disk interfaces was proposed and implemented by considering the incomparability between the milli-scale deformation of the suspension and the nano-scale variations of the air bearing gap. The suspension was modeled as a 3-DOF lumped parameters model. Realistic values of the parameters in the model were obtained from a comprehensive finite element analysis and verified with experiments. Three stages in the unloading process and their transitional conditions were analyzed using the FEM and the simplified lumped parameters model. Finite difference method and finite volume method were employed to solve the modified Reynolds equations governing the slider air bearing. Nonlinear variations of air bearing forces and moments with flying attitude in the L/UL processes were characterized and calculated by the proposed simple performance functions, which were easily obtained by function-fitting those discrete numerical solutions from the Reynolds equations with the minimal flying height and the pitch angle chosen as independent variables.